Novel biodegradable polydioxanone stents in a rabbit airway model - Novotny, Ladislav; Crha, Michal; Rauser, Petr; Hep, Aleš; Misik, Jan; Necas, Alois; Vondrys, David (Journal of thoracic and cardiovascular surgery, 2012)
OBJECTIVE: This study was undertaken to evaluate safety and biocompatibility of a novel biodegradable polydioxanone stent in a rabbit tracheal model. Metallic and silicone stents represent standard therapeutic approaches for hollow organ stenosis, although complications have been reported repeatedly. Biodegradable stents could reduce the risks associated with this procedure while still achieving the purpose of maintaining lumen patency. METHODS: A commercially available polydioxanone suture strand with a long safety record was used to manufacture the self-expanding stents. The polydioxanone stents were then implanted bronchoscopically and under fluoroscopic guidance into the tracheas of white rabbits (N = 25). Periodic clinical examination was performed. Histopathologic examination concluded the study for the 5 experimental groups at 3, 4, 5, 10, and 15 weeks after implantation. RESULTS: There were no unexpected deaths and no stent displacements during the study. The animals remained in good condition, without stent debris expectoration. Macroscopic examination revealed that the tracheal lumen stayed open. Histologic examination showed that tracheal damage score was highest 5 weeks after stenting, including in-stent necrosis of the epithelium. Stent degradation was complete with no remnants after 10 weeks, leaving the trachea completely healed at 15 weeks after implantation. CONCLUSIONS: This animal airway model has demonstrated acceptable safety and biocompatibility of this novel biodegradable polydioxanone stent. We suggest that polydioxanone stenting be used for further clinical studies for cases in which complete stent degradation after temporary airway treatment is desirable.
Keywords: protézy - design; modely u zvířat; fluoroskopie; Absorbable Implants; polydioxanon; Materials Testing; trachea; Stents; intervenční radiografie; Female; Radiography, Interventional; stenty; vstřebatelné implantáty; Polydioxanone; Trachea; testování materiálů; králíci; Time Factors; ženské pohlaví; bronchoskopie; Animals; zvířata; Fluoroscopy; Prosthesis Design; Rabbits; Models, Animal; časové faktory; Bronchoscopy